Salinity tolerance in Phaseolus species during early vegetative growth - Bayuelo Jiménez, Jeannette Sofia; Debouck, Daniel G.; Lynch, Jonathan P. (Wiley, 2002)
The genus Phaseolus includes important cultivated species as well as wild species with diverse ecological adaptations. Characterization of the ecological adaptations of the wild species would be useful for improved understanding, conservation, and utilization of these genetic resources. Salinity tolerance during vegetative growth was evaluated for 132 accessions for 14 wild Phaseolus species (P. acutifolius A. Gray, P. angustissimus A. Gray, P. carteri Freytag & Debouck, P. filiformis Bentham, P. glabellus Piper, P. leptostachyus Bentham, P. lunatus L., P. micranthus Hook & Arnold, P. microcarpus Mart, P. mcvaughii A. Delgado, P. oligospermus Piper, and P. vulgaris L.) and 11 accessions representing five cultivated species (P. acutifolius, P. coccineus L., P. lunatus L., P. polyanthus Greenman, and P. vulgaris) in nutrient solution containing 0 and 180 m M sodium chloride for 21 d. When plants were salinized after the emergence of the first trifoliate leaf, wild accessions of P. acutifolius, P. filiformis, P. lunatus, and P. vulgaris showed a wide range of variation in their salinity tolerance as defined by total dry weight reduction (PR) as a percentage of the unsalinized controls, salt susceptibility index (SSI), and root: shoot ratio (RSR). SSI and PR were correlated positively, indicating either trait could be used to select salt-tolerant accessions. Cluster analysis revealed substantial intraspecific and interspecific variation in salinity tolerance. Salinity tolerance was observed in wild P. micranthus, P. mcvaughii, P. lunatus, cultivated P. coccineus, and several accessions of wild P. filiformis, and P. vulgaris Of these, P. filiformis was noteworthy in having 9 of 11 accessions rated as highly tolerant. Wild P. vulgaris was more salinity tolerant than the three cultivated P. vulgaris accessions included in the study. Many tolerant accessions originated in arid, coastal, or saline areas. We conclude that the genus Phaseolus has substantial diversity in salinity tolerance.